Physical chemistry - Mortimer, Robert G. ([S.l.] : Benjamin-Cummings Publishing Company, 1992)
The unifying theme of "systems, states and processes" helps to integrate the diverse topics of physical chemistry by providing a common point of view for discussing each topic. Mortimer presents fundmental principles logically, with sufficient mathematical details to explain the principles, supplying users, at the same time, with the background information they need to apply the mathematics.